KEKUASAAN POLITIK ISLAM DI ANDALUSIA: PINTU GERBANG MENUJU RENAISANCE EROPA - Faidi, Ahmad (Al-Ijtima`i: International Journal of Government and Social Science, 2021)
The triumph of Islamic politics in Andalusia (Spain) is one of the most glorious historical assets of Islam. In addition to the glory of Islam in Baghdad, Andalusia became an important civilization milestone as a bridge for Europe to pick up the enlightenment and golden phase. Although, the contribution of Islam to the glory of Modern Europe is not widely echoed by Western historians, the traces of its history cannot be erased. Through the works of Muslim intellectuals, such as Ibn Rushd, Ibn Bajah, Ibn Khaldun, and so on, Europeans were reminded of the classical traditions of their ancestors. The study of Islamic philosophy initiated by Muslim philosophers succeeded in reviving the classical tradition of Greek philosophy. This kind of scientific climate later became the trigger for the birth of the reform, renaissance, and modernization movements in mainland Europe. Undeniably, the political and intellectual triumph of Islam in Andalusia, which was geographically more accessible to Europeans than the Abbasids in Baghdad, became an important bridge for the rise of Europe to the pinnacle of modern civilization.